MOTIVATION AND ORGANIZATIONAL CULTURE ON PERFORMANCE WITH SELF-EFFICACY MEDIATION - Tri Mardiana; Sucahyo Heriningsih (Modus, 2016)
The study aims to determine firstly the direct effect of motivation on performance,secondly the indirect effect of motivation on performance mediated by self efficacy, thirdlythe direct influence of organizational culture on the performance, and lastly the indirectinfluence of organizational culture on performance mediated by self-efficacy. The subjectsof this study are 60 women from the group of cashew producer. Hence, the samplingtechnique uses Census and the data collection method uses semi-structured interviews andquestionnaires. The data analysis uses Simple Linear Regression and Path Analysis. Basedon the data processing results, it shows: 1) the direct effect of motivation on the performanceare at 0,287; 2) the indirect effect of motivation on performance mediated by self efficacyare at 0.440; 3) the direct effect of organizational culture on the performance are at 0,260;and 4) the indirect influence organizational culture on performance mediated by selfefficacymediated are at 0.426.Therefore, it can be concluded that self-efficacy can help in overcoming the existingproblems in the organization, because self-efficacy encourage the efforts to improveperformance. Within strong, dynamic, and positive motivation and organizationalculture, one’s performance will definitely increase and shows good progress.Keywords: motivation, organizational culture, performance, self efficacy mediation.